2022
DOI: 10.1093/nar/gkac859
|View full text |Cite
|
Sign up to set email alerts
|

HiChIPdb: a comprehensive database of HiChIP regulatory interactions

Abstract: Elucidating the role of 3D architecture of DNA in gene regulation is crucial for understanding cell differentiation, tissue homeostasis and disease development. Among various chromatin conformation capture methods, HiChIP has received increasing attention for its significant improvement over other methods in profiling of regulatory (e.g. H3K27ac) and structural (e.g. cohesin) interactions. To facilitate the studies of 3D regulatory interactions, we developed a HiChIP interactions database, HiChIPdb (http://hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Our CNCC-specific regulations further prioritized only two SNPs (‘16:87237097’, ‘16:87236947’) located in this CNCC-specific RE, which may influence the expression of FOXC2 and the brain shape phenotypes. We checked the chromatin loops in the database of HiChIP ( Zeng et al, 2022 ) and found that this SNP-associated regulation of FOXC2 was supported by a HiChIP loop in brain tissues to link this SNP locus and FOXC2 promoter. This example showed the power of SpecVar to interpret the genetic variants’ association with phenotypes by detailed regulatory networks in relevant tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Our CNCC-specific regulations further prioritized only two SNPs (‘16:87237097’, ‘16:87236947’) located in this CNCC-specific RE, which may influence the expression of FOXC2 and the brain shape phenotypes. We checked the chromatin loops in the database of HiChIP ( Zeng et al, 2022 ) and found that this SNP-associated regulation of FOXC2 was supported by a HiChIP loop in brain tissues to link this SNP locus and FOXC2 promoter. This example showed the power of SpecVar to interpret the genetic variants’ association with phenotypes by detailed regulatory networks in relevant tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the current interaction predictions (e.g., DTIs) do not consider the causal interaction where one drug is involved in a biological or biochemical process to directly or indirectly affect a protein. Identifying such direct interactions and indirect interactions by causal inference method [64] could help us better understand the related biological or chemical pathways or mechanisms. Furthermore, based on complex geneprotein-drug-disease heterogeneous networks constructed from multiple genomics databases [65][66][67], combining sequence and structural features of proteins/ targets with association features in complex graphs through heterogeneous graph convolution networks would be a direction that could be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Such Example is ChromLoops [ 119 ] [https://3dgenomics.hzau.edu.cn/chromloops], an integrated dataset for high‐quality chromatin loops from 1030 datasets across 366 samples from 13 species from ChIA‐PET, HiChIP and PLAC‐Seq datasets. HiChIPdb [ 120 ] [http://health.tsinghua.edu.cn/hichipdb/] contains more than 260 million HiChIP interactions from 200 HiChIP experiments for 208 cell type at variable 1/5/10/50 kb resolution processed by FitHiChIP [ 121 ] and Hichipper [ 122 ] computational pipeline for loop calling. CohesinDB [ 123 ] [https://cohesindb.iqb.u-tokyo.ac.jp] is a multi‐omics database summarising information for Cohesin Protein in human cells.…”
Section: Exploring Nuclear Organization With 3c‐based Methodsmentioning
confidence: 99%